1996
DOI: 10.1177/172460089601100203
|View full text |Cite
|
Sign up to set email alerts
|

CA 19.9, CA 242 and CEA in the Diagnosis and Follow-up of Pancreatic Cancer

Abstract: The diagnosis of pancreatic cancer is usually made in the advanced stages of the disease when the prognosis is poor. We compared the behavior of CA19.9, CEA and the newly proposed mucin CA242 in a consecutive series of 42 pancreatic carcinomas. A control group was recruited of 21 patients with benign pancreatic diseases. With the recommended cutoffs (37 U/ml for CA19.9, 20 U/ml for CA242 and 8 ng/ml for CEA) we obtained a specificity of 90% for CA19.9 and of 85% for CA242 and CEA. The sensitivity was 85.7% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
1
19
2
1
Order By: Relevance
“…The results were promising and CA 242 has shown sensitivities and specficities similar to those of CA 19-9 and CA 50. For this study we colklcte a large series of 179 patients with pancreatic cancer, enabling Our study confirms previous obsations that the assay parameters of CA 242 are similar to those of CA 19-9 in the primary diagnosis of pancreatic cancer (Kuusela et al, 1991;Banfi et al, 1993;R6thlin et al, 1993). The highest serum levels of CA 242 and CA 19-9 were found in patients with unresectable dies, which can be diagnosed by other clinical, radiological and laboratory investigations rather easily.…”
Section: Ca 242 In Benign Diseasessupporting
confidence: 85%
See 1 more Smart Citation
“…The results were promising and CA 242 has shown sensitivities and specficities similar to those of CA 19-9 and CA 50. For this study we colklcte a large series of 179 patients with pancreatic cancer, enabling Our study confirms previous obsations that the assay parameters of CA 242 are similar to those of CA 19-9 in the primary diagnosis of pancreatic cancer (Kuusela et al, 1991;Banfi et al, 1993;R6thlin et al, 1993). The highest serum levels of CA 242 and CA 19-9 were found in patients with unresectable dies, which can be diagnosed by other clinical, radiological and laboratory investigations rather easily.…”
Section: Ca 242 In Benign Diseasessupporting
confidence: 85%
“…Preliminary results on the serum expression of CA 242 in pancreatic cancer were described in 1991 by Kuusela et al Later other small series including 24-68 patients were reported (Nilsson et al, 1992;Pasanen et al, 1992;Banfi et al, 1993;R6thlin et al, 1993). The results were promising and CA 242 has shown sensitivities and specficities similar to those of CA 19-9 and CA 50.…”
Section: Ca 242 In Benign Diseasesmentioning
confidence: 92%
“…It is worth noting, how ever, that the specificity of TPS was consider ably higher (73%). To some extent, our results are in contrast to those of Banfi et al [8] who found TPS highly sensitive (97.8%), but not specific (22%) among benign pancreatic dis eases. In that study, the cutoff level for TPS (40 U/l) was determined in healthy subjects using the 95th percentile.…”
Section: Discussioncontrasting
confidence: 56%
“…In the literature, few data are available on the utility of serum TPA and TPS assays in the diagnosis of pancreatic cancer. The sensitivity of TPA has varied from 36 to 96% and the specificity from 67 to 92% [5][6][7], and the sensitivity of TPS was found to be 97.8% and the specificity between 22 and 88% [8]. Lack of specificity has been one of the problems in the use of the serum tumor mark ers in pancreatic cancer [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies CA 19-9 has been found to be superior to TPS (16)(17)(18), whereas in another study the contrary was shown (19). We found that the AUC was slightly higher for TPS than for CA19-9 and CEA, but the differences were not significant.…”
Section: Discussioncontrasting
confidence: 42%